A Few Notes on Hegel and Nurettin Topçu’s Concept of the State - Jalilzada, Khayyam (Scholarya Demo Journal of Ruby, 2021)
This study focuses on the "concept of the state" in Hegel's and Nurettin Topçu's philosophies. The issue of the state, which is central to political philosophy, is at the heart of both philosophers' thoughts. When we think of modem-era philosophers who developed theories about the state, the first name that comes to mind is the German philosopher Hegel. In Hegel's system, the state has a decisive role. Many studies on Hegel's system have been conducted in Western languages, and some of these have been translated into Turkish. Beyond this, Hegel's state theory has been the subject of independent research and articles. Although issues related to politics have been discussed in Turkish thought, and opinions about the relationships of politics with other fields have been expressed, it appears difficult to say that studies on politics in the modem period are sufficient. We can say that Nurettin Topçu, a modern-day representative of Turkish thought, advanced significant views on political issues, particularly those concerning the state. Nurettin Topçu made the issue of the state the subject of his thought in various articles on various occasions, attempting to bridge the gap in this field, and his views on the state inspired many studies. We will determine the same and different aspects of the meanings these two names attribute to will, human, nation, religion, and history in connection with the state in our study, where we will compare the conclusions of both philosophers in the context of state thought. Our main goal here will be to reveal as many similarities and differences as possible between Hegel's and Nurettin Topçu's ideas, and to open a more robust assessment of this issue. Nurettin Topçu employs Hegel’s definitions of the state in some of his works. While our research will focus on Nurettin Topçu's Hegel influence, we will also attempt to uncover the fundamental differences between them. As a result, it will be demonstrated that Hegel was a pioneer in the emergence of problems related to the modern state, and Nurettin Topçu is the name that offers a solution to these problems.